Biosorption of Pb(II) from Aqueous Solution Using Mushroom (Pleurotus ostreatus) Biomass and Spent Mushroom Substrate. (21st September 2020) - Eliescu, Andreea; Georgescu, Andreea Antonia; Nicolescu, Cristina Mihaela; Bumbac, Marius; Cioateră, Nicoleta; Mureșeanu, Mihaela; Buruleanu, Lavinia Claudia
Abstract: The potential of Pleurotus ostreatus mushroom and its spent substrate were investigated for the biosorption of lead (II) from aqueous solutions in both batch and dynamic experiments. After evaluation and optimization of the Pb(II) sorption parameters, the Pleurotus ostreatus spent substrate (POBM) showed a greater adsorption capacity (85.91 mg/g) compared to the original spores of Pleurotus ostreatus (PO) (57.73 mg/g). Biosorption equilibrium, kinetic and thermodynamic models were applied to investigate the mechanism of lead sorption on both of the biosorbents. In order to achieve a more complete characterization, scanning electron microscopy – energy dispersive X-ray spectroscopy (SEM-EDX), Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) analysis were also performed. The Pleurotus ostreatus spent substrate biomass was used to remove Pb(II) from aqueous solution by the use of a fixed-bed column. The breakthrough curves at two concentrations equal to 50 and 100 mg/L were determined and analyzed using the Thomas and Yoon-Nelson theoretical models. The reusability properties of the biosorbents were determined using five cycles of adsorption and desorption. The applicability of the mushroom spent substrate as a biosorbent for Pb(II) removal from real wastewater was characterized in a continuous system in which 1 g of biomass allowed the purification of 2.4 L of lead contaminated water with 93% metal removal efficiency, confirming the suitability of this approach for large-scale applications.